2009
DOI: 10.1515/znb-2009-0109
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Polarized Phosphorus–Phosphorus Bonds by Alkynes: Rational Synthesis of Unsymmetrical 1,2-Bisphosphine Ligands and Their Complexes

Abstract: The reactions of 1,1-diamino-2,2-diphenyl-substituted diphosphines featuring various degrees of P-P bond polarization with different alkynes were investigated. All diphosphines reacted with alkynes carrying one or two electron withdrawing carboxylic ester moieties under cleavage of the P-P bond and stereospecific phosphinyl-phosphination at the triple bond to give unsymmetrical ethane-1,2- bisphosphines. Several of the products were further converted into chelate complexes upon reaction with group-10 metal dih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 0 publications
4
35
0
Order By: Relevance
“…The N-heterocyclic diphosphine 7 was synthesized by analogy to 2a, b and 4 [24] via metathesis of 6 with lithium diphenylphosphide. Although the reaction proceeded in almost quantitative yield (by 31 P NMR), we failed to isolate the product by crystallization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The N-heterocyclic diphosphine 7 was synthesized by analogy to 2a, b and 4 [24] via metathesis of 6 with lithium diphenylphosphide. Although the reaction proceeded in almost quantitative yield (by 31 P NMR), we failed to isolate the product by crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…31 P NMR studies revealed that quantitative conversion of the starting material into a single addition product 16 is observed even at room tempera- ture. The Z-configuration at the double bond has been derived from the observation of a characteristically large [24,44] 3 J PP coupling constant of 94 Hz. The assigned molecular structure was corroborated by conversion of 16 into the chelate complexes 17a, b upon treatment with (cyclooctadiene)palladium dichloride or anhydrous nickel dichloride at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PPh 2 ) and cyclic (e.g. phospholyl) substituents [39,43,44] . In several cases, coupling of the P-chloro-heterocycle with trimethylsilyl phosphines was feasible, although longer reaction times may affect the yields and the reaction is presumably not generally applicable [43] .…”
Section: Substituent Displacement Reactionsmentioning
confidence: 99%
“…phospholyl) substituents [39,43,44] . In several cases, coupling of the P-chloro-heterocycle with trimethylsilyl phosphines was feasible, although longer reaction times may affect the yields and the reaction is presumably not generally applicable [43] . Coupling of a P-chloro-1,3,2-diazaphospholene with a P-stannyl-phosphine via dehydrostannylation has been reported in one case [45] but this reaction is likewise not generally applicable and its reversion (i.e., cleavage of the P-P bond in a phosphinyl-NHP upon reaction with trimethylstannyl chloride) has likewise been observed [39] .…”
Section: Substituent Displacement Reactionsmentioning
confidence: 99%